EVALUATION OF THE CIPPO-BASED ONE TEACHER ONE INNOVATION PROGRAM AT SLB DHARMA WANITA KEBONSARI AND SLB PUTRA IDHATA IN MADIUN REGENCY - Yomang Sahara; Muhamad Sholeh; Nunuk Hariyati; Amrozi Khamidi; Ainur Rifqi; Ruqoyyah Fitri (LP2M IAI Al-Khairat Pamekasan, 2026)
Inclusive education requires teachers to design learning activities that meet the needs of students with special needs. The One Teacher One Innovation Program at SLB Dharma Wanita Kebonsari and SLB Putra Idhata in Madiun Regency was implemented to improve teacher competencies while producing contextual learning innovations. This study evaluated the program using the CIPPO model with a qualitative multi–case study approach through in-depth interviews, observations, and documentation, analyzed using the interactive model of Miles and Huberman. The results show that the program aligns with the need to enhance teacher competencies and is supported by adequate learning facilities and school leadership. Implementation took place systematically through planning, execution, and continuous supervision. The resulting learning innovations succeeded in increasing student interest and engagement. In addition, the outcomes of the study indicate increased self-confidence and professional appreciation among teachers. Another significant impact was observed in graduates with special needs who were involved in the innovation products. They demonstrated real improvements in skills such as self-care, literacy, communication, and vocational abilities, making them better prepared for everyday life after graduation and able to apply these skills independently outside of school. These findings affirm that the program not only improves the quality of learning but also provides long-term benefits for the development of competencies among students with special needs.